Threat or treat for tourism organizations? The Copenhagen Zoo social media storm. (15th August 2019) - Rydén, Pernille; Kottika, Efthymia; Hossain, Muhammad; Skare, Vatroslav; Morrison, Alastair M.
Abstract: Social media have emerged as a game changer for tourism by empowering consumers to collectively approve or oppose organizational behaviors. When consumers rise against organizations, social media storms (SMSs) can be an outcome. This research proposes a conceptual framework to help tourism organizations understand SMSs and to guide more effective decision making. Contextualized by a case study of the Copenhagen Zoo, it is shown how and why SMSs are an expression of negative consumer empowerment that brings challenges as well as opportunities. As demonstrated, an SMS can lead to a helix for value creation for the organization, consumers, and society.